Pelatihan Pengukuran Dimensi Pohon dan Pembuatan Label Pohon QR Code di Hutan Adat Ghimbo Pomuan - Ikhsani, Hanifah; Ikhwan, Muhammad; Ika Lestari (Lentera Pengabdian, 2023)
Sustainable forest management and support for the preservation of honey bee cultivation habitat requires collecting forest potential by measuring tree dimensions and presenting them on tree information labels. Furthermore, partners also do not have the knowledge and skills regarding measuring tree dimensions, namely measuring tree diameter and height and making QR Code tree information labels. Therefore, the service team provides a solution by increasing partners' knowledge by holding socialization about the meaning and benefits of measuring tree dimensions, the tools used in measuring tree dimensions. The team also improved partner skills by providing training on measuring tree dimensions and making QR Code tree information labels. The stages of community service carried out are the socialization of the meaning and benefits of measuring tree dimensions, the tools used in measuring tree dimensions, the advantages and disadvantages of tree dimension measurement tools and how to use tree dimension measurement tools. The team also conducted training on using tree dimension measurement tools, making QR Code tree information labels containing species, families, Latin and local names, tree coordinates, tree uses and photos with practice and field assistance as well as evaluations using questionnaires and observing partners' skills. After the service is completed, partners have or increase their knowledge about tree diameter and height, tools used for measuring tree diameter and height, how to use phiband and hagameter and knowledge of making QR Code tree labels of 89.16%. Partners have also been able to measure tree dimensions and make QR Code tree labels according to the knowledge they have received.